Identity theft in South Africa - Ncube, Caroline B (AHRC Research Centre for Studies in Intellectual Property and Technology Law, 2005)
Paper presented by Ncube for the Privacy Workshop, chaired by Edwards and held in September 2005.
Keywords: Intellectual Property Law; South Africa; Privacy